Rapid Pacing Decreases L-type Ca2+ Current and Alters Cacna1c Isogene Expression in Primary Cultured Rat Left Ventricular Myocytes - Ritzer, Anne; Röschl, Tobias; Nay, Sandra; Rudakova, Elena; Volk, Tilmann (Journal of Membrane Biology, 2023)
The L-type calcium current (ICaL) is the first step in cardiac excitation–contraction-coupling and plays an important role in regulating contractility, but also in electrical and mechanical remodeling. Primary culture of cardiomyocytes, a widely used tool in cardiac ion channel research, is associated with substantial morphological, functional and electrical changes some of which may be prevented by electrical pacing. We therefore investigated ICaL directly after cell isolation and after 24 h of primary culture with and without regular pacing at 1 and 3 Hz in rat left ventricular myocytes. Moreover, we analyzed total mRNA expression of the pore forming subunit of the L-type Ca2+ channel (cacna1c) as well as the expression of splice variants of its exon 1 that contribute to specificity of ICaL in different tissue such as cardiac myocytes or smooth muscle. 24 h incubation without pacing decreased ICaL density by 10% only. Consistent with this decrease we observed a decrease in the expression of total cacna1c and of exon 1a, the dominant variant of cardiomyocytes, while expression of exon 1b and 1c increased. Pacing for 24 h at 1 and 3 Hz led to a substantial decrease in ICaL density by 30%, mildly slowed ICaL inactivation and shifted steady-state inactivation to more negative potentials. Total cacna1c mRNA expression was substantially decreased by pacing, as was the expression of exon 1b and 1c. Taken together, electrical silence introduces fewer alterations in ICaL density and cacna1c mRNA expression than pacing for 24 h and should therefore be the preferred approach for primary culture of cardiomyocytes. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-14
Keywords: Cacna1c; Cardiac memory; Regional differences; Remodeling